Wakaf Esensi Solutif Perbaikan Pendidikan: Jawabah Dilema Lulusan Pendidikan Islam Antara Output, Outcome dan Produk - Hasan H A Buro (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
Failure and deterioration of Islamic education can be seen from the reflection of infrastructure, funds, quality educators who are far from expectations should, resulting in to create output. wakaf has a positive outlook, if it is well managed to improve the quality and progress of Islamic education in the future. This study aims to describe: how wakaf as the essence of solutive improvement of education which is an answer to the dilemma of education graduates between output, outcome and product. This study uses